2003
DOI: 10.1128/aem.69.9.5453-5462.2003
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Flax Roots and Early Physiological Responses of Flax Cells Inoculated with Pathogenic and Nonpathogenic Strains of Fusarium oxysporum

Abstract: Fusarium oxysporum includes nonpathogenic strains and pathogenic strains that can induce necrosis or tracheomycosis in plants. The objective of this study was to compare the abilities of a pathogenic strain (Foln3) and a nonpathogenic strain (Fo47) to colonize flax roots and to induce early physiological responses in flax cell culture suspensions. Both strains colonized the outer cortex of the root; however, plant defense reactions, i.e., the presence of wall appositions, osmiophilic material, and collapsed ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 72 publications
5
66
1
1
Order By: Relevance
“…The first reports on visualization focused on the colonization of the root tissue by either a pathogenic (Olivain and Alabouvette 1999;Olivain et al 2003), or a nonpathogenic Fusarium strain Alabouvette 1997, Olivain et al 2003) of plants growing in nutrient solutions and using electron microscopy. The use of a β-glucuronidase construct allowed quantification of the nonpathogenic F. oxysporum SA70 on roots of tomato plants grown in soil or potting material (Bao et al 2000;Eparvier and Alabouvette 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The first reports on visualization focused on the colonization of the root tissue by either a pathogenic (Olivain and Alabouvette 1999;Olivain et al 2003), or a nonpathogenic Fusarium strain Alabouvette 1997, Olivain et al 2003) of plants growing in nutrient solutions and using electron microscopy. The use of a β-glucuronidase construct allowed quantification of the nonpathogenic F. oxysporum SA70 on roots of tomato plants grown in soil or potting material (Bao et al 2000;Eparvier and Alabouvette 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of novel functions of active oxygen species (AOS) have revealed that, in addition to arresting pathogen proliferation in planta, AOS are involved in cell wall reinforcement (Olivain et al, 2003) and callose deposition (Huckelhoven et al, 1999). Moreover, they are able to act as signaling molecules (Alvarez et al, 1998;Bolwell et al, 1995;Chamnongpol et al, 1998;Rhee et al, 2010;Tenhaken et al, 1995;Wojtaszek, 1997).…”
Section: Programmed Cell Death (Pcd) Is Ubiquitous In All Organismsmentioning
confidence: 99%
“…Recently, novel functions of AOS have been investigated. Besides arresting pathogen proliferation in planta, AOS are involved in cell wall reinforcement (Olivain et al, 2003), callose deposition (Huckelhoven et al, 1999), and acts to signal molecules in systemic translocation of acquired resistance (Bolwell et al, 1995(Bolwell et al, , 1998Tenhaken et al, 1995;Wojtaszek, 1997;Alvarez et al, 1998;Chamnongpol et al, 1998). Similar to previously known plant defense activators, methyl viologen and mercuric chloride promote oxidative damage and chlorosis-induced plant defense responses (van Loon, 1975;Lund et al, 1993;Strobel and Kuc, 1995).…”
mentioning
confidence: 94%